Application of Origin Rules in Kaesong Industrial Complex, North Korea - Kim Na Young (Fakultas Hukum Universitas Gadjah Mada, 2009)
Under the expansion of regional economic integration, a product may be assembled in more than one country, creating the problem to determine the origin of the product. This paper aims to analyze the issue to recognize products manufactured in Kaesong Industrial Complex, North Korea, as products originating from South Korea. Sebagai akibat dari berkembangnya kesatuan-kesatuan ekonomi regional, suatu produk dapat diproduksi di lebih dari satu negara. Hal ini menimbulkan masalah dalam menentukan asal negara produk tersebut. Penelitian ini bertujuan untuk mempelajari isu untuk menetapkan produk-produk dari Kompleks Industri Kaesong, Korea Utara, sebagai produk yang berasal dari Korea Selatan.